2020
DOI: 10.1007/s00701-020-04615-z
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of retractions in neurosurgery and allied clinical and basic science specialties

Abstract: Background As the volume of scientific publications increases, the rate of retraction of published papers is also likely to increase. In the present study, we report the characteristics of retracted papers from clinical neurosurgery and allied clinical and basic science specialties. Methods Retracted papers were identified using two separate search strategies on PubMed. Attributes of the retracted papers were collected from PubMed and the Retraction Watch database. The reasons for retraction were analyzed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Different approaches have been used to identify postretraction citations, such as after 1 month ( Mott et al, 2019 ), after 6 months ( Hamilton, 2019 ), and after the calendar year of retraction ( Budd et al, 2011 , 2016 ; Madhugiri et al, 2021 ; Pfeifer & Snodgrass, 1990 ). Here we operationalize a postretraction citation as a citation made after the calendar year of retraction.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different approaches have been used to identify postretraction citations, such as after 1 month ( Mott et al, 2019 ), after 6 months ( Hamilton, 2019 ), and after the calendar year of retraction ( Budd et al, 2011 , 2016 ; Madhugiri et al, 2021 ; Pfeifer & Snodgrass, 1990 ). Here we operationalize a postretraction citation as a citation made after the calendar year of retraction.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Madhugiri et al (2021) examined citations to 191 retracted papers in clinical neurosurgery as well as in allied clinical and basic science specialties. They reported that postretraction citations accounted for 50% of all the citations received by the retracted papers ( Madhugiri et al, 2021 ). Rubbo et al (2019) and Theis-Mahon and Bakker (2020) studied 238 retracted engineering articles and 136 retracted dentistry articles, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations